Literatura v luči medijsko orientirane sistemske teorije - Perenič, Urška (Slavistična revija, 2009)
A media-oriented systemic tretment of literature offers a satisfactory answer to the question how it is possible in literary research to resolve the gap between essentialism and relativism and to include various aspects of literature. In order to capture the aesthetic and socio-historical dimension of literature, it is first necessary to define the protagonists of literary action and the text. Of key relevance is also concept of the medium, which includes semiotic communicative instruments, tehchnologies, social institutions with the influence of economic, legal, political ideological, cultural and other systems. On this basis, the author proposes a concrete content analysis, which is supported to define the relationship between the text and the context.
Keywords: constructive understanding of the medium; content analysis; empirical literary criticism; empirična literarna znanost; konstruktivistično pojmovanje medija; literarna teorija; media-oriented systemic theory of literature; medijsko orientirana sistemska teorija literature; tematsko kodiranje; thematic coding; theory of literature; vsebinska analiza